Professor Slutsky's Theory of Consumers' Choice - Allen, R. G. D. (Review of Economic Studies, 1936)
Professor Slutsky's Theory of Consumers' Choice Get access R. G. D. Allen R. G. D. Allen London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 2, February 1936, Pages 120–129, https://doi.org/10.2307/2967502 Published: 01 February 1936